We are asked to find \( [\mathbf{a} \, \mathbf{b} \, \mathbf{c}] = |\mathbf{a} \cdot (\mathbf{b} \times \mathbf{c})| \).
Step 1: Compute the cross product \( \mathbf{b} \times \mathbf{c} \) and then dot it with \( \mathbf{a} \). \[ [\mathbf{a} \, \mathbf{b} \, \mathbf{c}] = \left| \begin{vmatrix} 1 & 0 & -1 \\ x & 1 & 1 - x \\ y & x & 1 + x - y \end{vmatrix} \right| \] Simplifying this determinant: \[ = 1 + x - y - x^2 + x^2 - y = 1 \] Thus, \( [\mathbf{a} \, \mathbf{b} \, \mathbf{c}] = 1 \), which is independent of both \( x \) and \( y \).